The Gospel of Judas : rewriting early christianity - Gathercole, Simon (Oxford University Press, 2007)
The newly-discovered ancient text of the Gospel of Judas offers a picture of Judas Iscariot radically different from the Church's traditional understanding of him as the arch-traitor. Simon Gathercole's book, which includes a translation and a running commentary, gets behind the hype which the Gospel of Judas has attracted. - ;J̀udas' is synonymous with t̀raitor'. But a newly-discovered ancient text of the Gospel of Judas offers a picture of Judas Iscariot radically different from the Church's traditional understanding of him, and maintains that far from being the infamous betrayer, Judas was.